2010
DOI: 10.1124/jpet.110.175927
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Meclizine on the Activity of Human Pregnane X Receptor and Constitutive Androstane Receptor

Abstract: Conflicting data exist as to whether meclizine is an activator of human pregnane X receptor (hPXR). Therefore, we conducted a detailed, systematic investigation to determine whether meclizine affects hPXR activity by performing a cell-based reporter gene assay, a time-resolved fluorescence resonance energy transfer competitive ligand-binding assay, a mammalian twohybrid assay to assess coactivator recruitment, and a hPXR target gene expression assay. In pregnane X receptor (PXR)-transfected HepG2 cells, mecliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
(61 reference statements)
2
27
0
Order By: Relevance
“…A hCAR-dependent mammalian two-hybrid assay was performed as described in detail previously (Lau et al, 2011). At 5 h after plating, HepG2 cells were cotransfected with pVP16-hCAR-WT-LBD (40 ng/well), pVP16-hCAR-SV23-LBD (40 ng/well), or pVP16 empty vector (40 ng/well) along with a coactivator expression plasmid (10 ng/well), pCMV6-XL4-hRXR␣ (10 ng/well), pGL4.74[hRluc/TK] internal control plasmid (10 ng/well), and pFR-luc reporter plasmid (100 ng/well).…”
Section: Methodsmentioning
confidence: 99%
“…A hCAR-dependent mammalian two-hybrid assay was performed as described in detail previously (Lau et al, 2011). At 5 h after plating, HepG2 cells were cotransfected with pVP16-hCAR-WT-LBD (40 ng/well), pVP16-hCAR-SV23-LBD (40 ng/well), or pVP16 empty vector (40 ng/well) along with a coactivator expression plasmid (10 ng/well), pCMV6-XL4-hRXR␣ (10 ng/well), pGL4.74[hRluc/TK] internal control plasmid (10 ng/well), and pFR-luc reporter plasmid (100 ng/well).…”
Section: Methodsmentioning
confidence: 99%
“…pGL3-basic-CYP2B1-luc reporter was generously provided by Dr. Thomas A. Kocarek (Wayne State University, Detroit, MI) (Kocarek and Mercer-Haines, 2002). pGL3-basic-CYP2B6-PBREM/XREM-luc reporter (Lau et al, 2011b) and pGL3-basic-CYP3A4-XREM-luc reporter (Lau et al, 2010) were constructed as described previously. All constructs were sequenced by the Nucleic Acid Protein Service Unit at the University of British Columbia (Vancouver, BC, Canada), and the identity of plasmids was confirmed by comparing their sequences with published sequences.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the treatment period, cultured human hepatocytes were washed with Hanks' balanced salt solution (HBSS) and incubated for 20 min at 37°C with 0.5 ml of HBSS containing bupropion (final concentration of 500 M) dissolved in DMSO (final concentration of 0.1% v/v in HBSS). The bupropion hydroxylation assay was performed using an ultraperformance liquid chromatography-tandem mass spectrometry assay as described previously (Lau et al, 2011b).…”
Section: Methodsmentioning
confidence: 99%
“…a well known peripheral benzodiazepine receptor ligand, PK11195, as a CAR inhibitor-the most potent inhibitor of CAR identified thus far (Li et al, 2008). Interestingly, all the known CAR inhibitors are also moderate-to-potent activators of PXR function, complicating expression levels of their shared target genes Moore et al, 2002;Huang et al, 2007;Li et al, 2008;Lau et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Clotrimazole (CLZ), meclizine, and androstanol are moderate inhibitors of CAR that function in both in vitro biochemical assays and cell-based transfection assays (Forman et al, 1998;Moore et al, 2000;Tzameli et al, 2000;Moore et al, 2002;Huang et al, 2004;Omiecinski et al, 2011). We and others, however, have observed that all these CAR inhibitors are also moderate to potent activators of PXR function Moore et al, 2002;Li et al, 2008;Lau et al, 2011).…”
Section: Introductionmentioning
confidence: 95%